The Influence of Digitalization Developments on the Character of Ma Mamba'ul Ulum Jurit Students - Mariawati, Mariawati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim of this research is to find out whether there is an influence of digitalization on the character of students at MA Mamba'ul Ulum Jurit. The data collection instruments used in this research were questionnaires and documentation. The questionnaire distributed previously has been tested for validity and reliability. Of the 51 questionnaires whose validity was tested, 18 valid questionnaires were obtained for the character variable, and 18 questionnaire items for the digitalization variable. The research method used is quantitative research with a sample size of 85 students. The analytical test used is simple linear regression. Before testing the hypothesis, there is a prerequisite test, namely the normality test, homogeneity test and linearity test. After the prerequisite tests are fulfilled, the analysis is then tested using simple regression analysis where the test results are obtained with a t test significance of 0.000, where the decision-making criteria is if the t test significance value is <0.05 then Ha is accepted, This means that there is an influence of digitalization on the character of students at MA Mamba'ul Ulum Jurit.